Modulation of autophagy in the protective effect of resveratrol on PM2.5‐induced pulmonary oxidative injury in mice. (20th September 2018) - Li, Yuan; Fu, Suming; Li, Enlai; Sun, Xianchao; Xu, Haie; Meng, Yu; Wang, Xiaoqian; Chen, Yue; Xie, Chunfeng; Geng, Shanshan; Wu, Jieshu; Zhong, Caiyun; et al.
Abstract : Ambient fine particulate matter (PM2.5) is capable of inducing pulmonary oxidative injury. Autophagy maintains basal cellular homeostasis and plays a critical role in the pathogenesis of lung diseases. Resveratrol, a natural polyphenol, is an effective antioxidant agent against particulate matter (PM)‐induced injuries. The current study was designed to investigate whether resveratrol can regulate autophagy in the process of PM2.5‐mediated pulmonary oxidative injury. In the mice model of PM2.5 exposure, we found that PM2.5 increased the contents of malondialdehyde (MDA) and nitric oxide (NO) while decreased the expression of nuclear factor erythroid‐2‐related factor 2 in the lungs. The levels of 8‐hydroxydeoxyguanosine and inflammatory cytokines were increased following PM2.5 exposure. Histological analysis of the lungs revealed inflammatory change in PM2.5 group. Meanwhile, PM2.5 triggered autophagy, as evidenced by the elevated expression of microtubule‐associated proteins light chain 3II, Beclin1 and p62. Transmission electron microscopy images showed that autophagosomes accumulated in the lungs after PM2.5 exposure. Furthermore, resveratrol intervention suppressed autophagy and attenuated the oxidative injury resulting from PM2.5 exposure. Our findings provided a valuable insight into the underlying mechanism for the protective effects of resveratrol against PM2.5‐induced lung injury, which involves suppression of the autophagic process.